Pengaruh Disiplin Kerja, Stress Kerja dan Kompensasi terhadap Kinerja Karyawan Perusahaan PT. Implora Sukses Abadi - Nidina Angelina Rahma; Agung Dwi Nugroho (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of work discipline, work stress, and compensation on employee performance at PT. Implora Sukses Abadi, a company engaged in the cosmetics industry and is experiencing rapid growth in Indonesia. The method used is a descriptive qualitative approach based on literature studies, with data obtained from scientific journals, human resource management books, and official company documents. The findings show that work discipline that is applied consistently can increase productivity and create a structured work environment. On the other hand, unmanaged work stress can hinder employee performance, although to a certain extent it can be a driver of work enthusiasm. Fair and proportional compensation has been proven to be the main motivator in increasing employee loyalty and performance. These three factors are synergistically related to each other in shaping individual and team performance. This study recommends strengthening discipline-based management, workload balance, and a transparent compensation system in order to maintain the company's competitiveness.